ANALISIS KETERKAITAN SERVICE LEVEL WAREHOUSE TERHADAP PEMENUHAN PERMINTAAN BARANG PADA PT ABC CABANG BANDUNG - Elisa Setianti; Nurillah Jamil Achmawati Novel (Jurnal Sekretaris dan Administrasi Bisnis, 2025)
This research analyzes the impact of warehouse service levels on meeting product demand at PT ABC Branch Bandung. The method used in this research is qualitative methodology with a case study approach. Data collection was conducted through participatory observation followed by analysis. The findings show that the warehouse service level at PT ABC averaged 92% during August, September, and October 2024. This value is influenced by the average supplier service level of 79%, resulting in suboptimal product demand fulfillment. This finding emphasizes the necessity of effective inventory management and supplier governance to enhance warehouse performance and maximize corporate profitability. This research provides strategic recommendations to improve inventory control and operational efficiency so that the company can better meet customer demands.